Cinical Significance of Androgen Receptor, CK-5/6, KI-67 and Molecular Subtypes in Breast Cancer. - GÜCİN, ZÜHAL; KAYAHAN, M; MEMMİ, NAİM; İDIZ, UO; Gucin, ZÜHAL; EROZGEN, F; MEMMI, NAİM; MUSLUMANOGLU, M (My University, 2014)
Objective: To detect the relationship between molecular subtypes of breast cancer with expressions of androgen receptor, cytokeratin 5/6 (CK5/6)and Ki-67. Materials and methods: Expressions of androgen receptor, CK-5/6 and Ki-67 were determined by immunohistochemistry in paraffin-embedded sections obtained from 86 invasive breast cancer cases of stages I/IIa/IIb in 4 molecular subtypes. Patients treated for recurrent disease and locally advanced disease were excluded. Results: Forty one luminal A cases, ie. positive estrogen receptor(ER) and/or progesteron receptor (PR) with negative epidermal growth factor receptor (HER2), 14 luminal B, ie. positive ER and/or PR and positive HER2, 14 HER2-enriched (HER2+), ie. negative ER and PR with positive HER2, and 17 triple negative (negative ER and PR and HER2) invasive breast cancers were included. Mean follow-up was 17.46±11.70 mo. Androgen receptor-negativity and CK5/6-positivity were significantly more common in HER2+ and triple negative groups. Ki-67 and histological grade were higher in HER2+ group, significantly. Two deaths were triple negative (P=0.04). Androgen receptor-negativity, CK5/6 and Ki-67 status did not affect survival or systemic metastases, significantly. All groups had local recurrences. Local recurrence was significantly associated with androgen receptor-negativity in luminal A and high Ki-67 value in HER2+ groups. Systemic metastases were significantly more common in triple negative and HER2+ groups. Conclusion: Molecular subtypes of breast cancer are prognostic and predictive. Androgen receptor is expressed more commonly in luminal subtypes with better prognosis and androgen receptor negativity is associated with development of local recurrence in luminal A cancers.